3-D Numerical simulation of water flow over a broad-crested weir with openings. (2nd November 2021) - Daneshfaraz, Rasoul; Minaei, Omar; Abraham, John; Dadashi, Sorayya; Ghaderi, Amir
ABSTRACT: The creation of an opening in a broad-crested weir body increases the discharge coefficient and reduces the water elevation behind the weir. In this study, three-dimensional numerical modeling is applied to investigate the water behavior, free-surface profiles, and velocity distributions over a broad-crested weir with one opening, two vertically arranged openings, and two horizontally arranged openings. The present study is limited to the above-described weir-opening arrangements. To determinate the most accurate turbulence model, results from the numerical simulation were compared with experimental data. Based on this comparison, the RNG turbulence model was chosen. The behavior of two horizontally arranged openings and the no-opening model were similar and critical flow occurred in two other models (one opening and two vertically arranged openings), downstream of the weir. Also, the maximum velocity in the models without openings was higher than in the other cases.